Scaling up experiential learning for water management - Meinzen-Dick, Ruth S.; Falk, Thomas; Sanil, Richu; ElDidi, Hagar; Zhang, Wei; Kosec, Katrina; Melesse, Mequanint B.; Duche, Vishwambhar (International Food Policy Research Institute, 2024)
Unsustainable water management is associated with reduced agricultural production and poverty, reduced ecosystem services and resilience, and insufficient and unreliable domestic water access. As a common pool resource with high subtractability and low excludability, water is easily depleted if no effective coordination exists among users to ensure provision and regulate withdrawals. This creates one of the greatest challenges for people living in semi-arid and arid environments. The majority of India’s population is estimated to face physical water scarcity for at least part of the year, with 600 million people living in areas of high to extreme water stress. As water management is highly complex, with many users sharing the same resource but often unknown to each other, stopping overuse is difficult, especially when it is more profitable to irrigate water-consumptive crops than water-conserving crops.